Comprehensive project management model to enhance software management success - Mohanarajah, S. (2020)
The management of software projects success with current project management models formally based and developed with traditional or plan-based, agile and hybrid management methodologies in dynamic flexibility and size complexity environments have not worked to its expectation in increasing the success rates in software projects over the last two decades in Malaysia. Traditional project management methodologies were plan driven and rigid in the implementation of Information Technology (IT) projects. The birth of modern project management with the introduction of the Agile Manifesto in 2001 had promised to better manage IT projects with its 4 values and 12 principles, but increase in software management success still appears to be elusive. The Agile Manifesto promised an improvement in the management of software success while studies of critical success and failure factors have also been used as quick solutions and not longterm robust improvements. Hybrid project management methodologies, which combined traditional or plan-based and agile methodologies, are being used but its feasibility as suitable methodologies is unclear in dynamic flexibility and size complexity environments. This scenario has created a need to review the software management success problem with more emphasis in the enhancement of software success management through studies on the management of traditional or plan-based, agile and hybrid models with dynamic flexibility and size complexity moderators to support contingency environments and close some of the gaps in current project management models. A comprehensive Project Management Model was proposed and developed with significant characteristics in traditional or plan-based, agile and hybrid methodologies in project environments that required dynamic flexibility and size complexity contingencies with an objective to enhance software management success. An empirical research methodology was used with a quantitative approach to collect data using questionnaires provided to software management practitioners managing software projects in industry. The data collected was analysed using the Statistical Package for the Social Sciences (SPSS) and the Partial Least Squares (PLS) tools with the Structural Equation Modeling (SEM) technique. The analysis from the tools and techniques assisted in evaluating the proposed comprehensive project management model with a set of software management characteristics that were significant in enhancing the management of success in software projects. The comprehensive project management model was statistically validated and provided to practitioners in industries. The model was found to be effective as it enhanced the success management of their current software projects both in the usage of methodologies and in dynamic flexibility and size complexity environments as contingencies. This study provided a major contribution to the software industry as previous studies of project management models were not comprehensive in integrating the various significant characteristics in software project management methodologies with dynamic flexibility and size complexity environments. The empirical and industry validation of the comprehensive project management model resulted in an increase in percentage by 73.56% and 82.15% respectively in software management success.